1987
DOI: 10.1111/j.1768-322x.1987.tb00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cytokeratin filaments and centriolar derivatives during ciliogenesis in the quail oviduct

Abstract: In the quail oviduct, the mature ciliated cells contain a well developed and polarized cytokeratin network which is bound to desmosomes and in close contact with the striated rootlets associated with basal bodies. In ovariectomized quail, the immature epithelial cells of oviduct present a rudimentary cytokeratin network associated with the centrioles of the diplosome (one of them forming a primary cilium) and with the short striated rootlets. The development of the cytokeratin network which occurs simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…We have observed that the formation of striated rootlets in the human oviduct epithelium starts around the time of ciliary budding, a result that is consistent with previous reports (Brenner and Anderson 1973;Lemullois et al 1987;Gaillard et al 1989). Fibrous granules have been assumed to be involved in rootlet formation in the ciliated epithelium of the rat (Sorokin 1968), monkey (Brenner and Anderson 1973), and quail (Lemullois et al 1987).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have observed that the formation of striated rootlets in the human oviduct epithelium starts around the time of ciliary budding, a result that is consistent with previous reports (Brenner and Anderson 1973;Lemullois et al 1987;Gaillard et al 1989). Fibrous granules have been assumed to be involved in rootlet formation in the ciliated epithelium of the rat (Sorokin 1968), monkey (Brenner and Anderson 1973), and quail (Lemullois et al 1987).…”
Section: Discussionsupporting
confidence: 91%
“…Fibrous granules have been assumed to be involved in rootlet formation in the ciliated epithelium of the rat (Sorokin 1968), monkey (Brenner and Anderson 1973), and quail (Lemullois et al 1987). The relationship appears to be the same in the epithelium of the human oviduct.…”
Section: Discussionmentioning
confidence: 98%
“…However, immu- nohistochemical studies have failed to show tubulin in these structures [Dirksen, 1991]. Although keratin has been identified in filaments associated with dense granules by immunoelectron microscopy [Lemullois et al, 1987], the composition of dense granules themselves has not been known. In the present study, both dense granules and fibrogranular complexes in ciliogenic cells were specifically labeled by R4109.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, depletion of z-tubulin does not affect binding of MTs to the basal feet, but it perturbs the assembly of the apical and subapical actin networks, which further suggests that basal feet connect BBs to the actin cytoskeleton (Turk et al 2015). Mature MCCs in the quail oviduct contain a well-developed cytokeratin network that binds to desmosomes and to the striated rootlets, suggesting that intermediate filaments could also participate in BB organization in these cells (Lemullois et al 1987).…”
Section: Ciliary Beat Orientation Bb Organizationmentioning
confidence: 99%